Associations of Preoperative Self-rated Symptoms of Anxiety and Depression on Length of Hospital Stay and Long-term Quality of Life in Patients Undergoing Cardiac Surgery. Issue 3 (31st May 2022) - Gorini, Alessandra; Giuliani, Mattia; L'Acqua, Camilla; Barbieri, Simone; Sisillo, Erminio; Veglia, Fabrizio; Tremoli, Elena
Abstract : Background: Anxiety and depression are often associated with cardiovascular diseases. Nevertheless, few study authors have investigated psychological effects on immediate and long-term cardiac surgery–related outcomes, such as surgical complications, length of hospital stay (LOS), and long-term health-related quality of life (HRQoL). Objectives: The aims of this study were to ( a ) investigate the role of preoperative symptoms of anxiety and depression in predicting LOS in a sample of surgical patients and ( b ) evaluate the impact of preoperative symptoms of anxiety and depression on the patients' HRQoL 3 months after surgery. Methods: One hundred fifty-one patients waiting for surgery were included. To evaluate symptoms of anxiety and depression, the Hospital Anxiety and Depression Scale was used. Multiple regression analyses were conducted to evaluate the impact of both clinical and psychological factors on LOS, whereas quantile regression was performed to assess their effect on the patients' HRQoL 3 months after surgery. Results: The multiple regression shows that EuroSCORE, length of endotracheal intubation, and anxiety symptoms predict LOS. The multiple quantile regression analyses also show that both symptoms of anxiety and depression predict a negative HRQoL up to 3 months after surgery. Conclusion: Preoperative symptoms of anxiety predict the patients' LOS, and both symptoms of anxiety and depression predict a scarce HRQoL 3 months after cardiac surgery. These results suggest the need for implementing presurgical in-hospital screening procedures for both symptoms of anxiety and depression. Finally, focused psychological interventions should be implemented for reducing inpatients' hospital LOS and improving their future quality of life.